2021
DOI: 10.1039/d1dt01716k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic activity of palladium complexes bearing N-heterocyclic carbenes (NHCs) and 1,4,7-triaza-9-phosphatricyclo[5.3.2.1]tridecane (CAP) ligands

Abstract: The synthesis and characterization of novel palladium complexes bearing N-heterocyclic carbenes (NHCs) and 1,4,7-triaza-9-phosphatricyclo [5.3.2.1] tridecane (CAP) are reported. These organometallic complexes can be easily obtained using two different synthetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…This abnormal behavior is also reflected to the CAP derivatives 1b-3b . As shown in Table 2 , their 31 P resonances are displaced upfield which is unusual among phosphane ligands but is also observed for other CAP complexes [ 12 ]. All complexes reported herein show a single 31 P peak demonstrating the absence of isomers, as expected.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…This abnormal behavior is also reflected to the CAP derivatives 1b-3b . As shown in Table 2 , their 31 P resonances are displaced upfield which is unusual among phosphane ligands but is also observed for other CAP complexes [ 12 ]. All complexes reported herein show a single 31 P peak demonstrating the absence of isomers, as expected.…”
Section: Resultsmentioning
confidence: 54%
“…A further feature that makes CAP particularly interesting is its stereoelectronic properties. CAP combines strong electron-donating ability with an extremely reduced steric hindrance (cone angle = 109°) [ 12 ] making this phosphine ligand unique compared to more classical tertiary phosphines.…”
Section: Introductionmentioning
confidence: 99%
“…The longer reaction time (usually 24 h) is attributed to the high ligand steric bulkiness as we have previously observed that the much smaller CAP ligand required only 15 minutes to complete this ligand substitution. 32 An alternative synthetic route to such compositions was explored starting from PdCl 2 (Scheme 1, Method B). However, for the reaction to proceed, the reaction temperature had to be raised to 60 °C and the operational solvent had to be changed to chloroform.…”
Section: Synthesis and Properties Of Phosphine Peppsi Complexesmentioning
confidence: 99%
“…31 Another example is the use of the CAP (1,4,7-triaza-9-phosphatricyclo[5.3.2.1]tridecane) ligand in the context of a PEPPSI architecture which did not display any reactivity in C-N coupling. 32 Therefore we were eager to investigate such complexes with more commonly utilized Buchwald biaryl phosphine ligands. Herein we report the synthesis, characterization and catalytic activity in C-N coupling of a series of phos-phine palladium PEPPSI and chloride dimer complexes bearing the known Buchwald ligands, RuPhos, SPhos and XPhos, as ancillary ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Britvin and coworkers reported the synthesis of the new cage-like water soluble phosphine 1,4,7-triaza-9phosphatricyclo[5.3.2.1]tridecane, to which they gave the acronym of CAP (Figure 1). [26] Although examples of CAP complexes of Au, [26a] Pt and Pd, [27,28] Tc and Re, [29] and Rh [30] were reported, its coordination chemistry with Ru is still underdeveloped. We recently reported the synthesis of the Ru-arene CAP complexes [RuCl 2 (η 6 -p-cymene)(CAP)] (RACAPÀ C) and [RuCl (η 6 -p-cymene)(L)(CAP)]PF 6 (L = CAP or MeCN), that showed to be active in vitro anticancer agents.…”
Section: Introductionmentioning
confidence: 99%